Synthesis of trifluoromethyl-substituted pyrazolo[4,3-c]pyridines – sequential versus multicomponent reaction approach - Palka, Barbara; Di Capua, Angela; Anzini, Maurizio; Vilkauskaité, Gyté; Šačkus, Algirdas; Holzer, Wolfgang (Beilstein Journal of Organic Chemistry, 2014)
A straightforward synthesis of 6-substituted 1-phenyl-3-trifluoromethyl-1H-pyrazolo[4,3-c]pyridines and the corresponding 5-oxides is presented. Hence, microwave-assisted treatment of 5-chloro-1-phenyl-3-trifluoromethylpyrazole-4-carbaldehyde with various terminal alkynes in the presence of tert-butylamine under Sonogashira-type cross-coupling conditions affords the former title compounds in a one-pot multicomponent procedure. Oximes derived from (intermediate) 5-alkynyl-1-phenyl-3-trifluoromethyl-1H-pyrazole-4-carbaldehydes were transformed into the corresponding 1H-pyrazolo[4,3-c]pyridine 5-oxides by silver triflate-catalyzed cyclization. Detailed NMR spectroscopic investigations (1H, 13C, 15N and 19F) were undertaken with all obtained products.
Keywords: microwave-assisted reactions; multicomponent reactions; NMR (1H; 13C; 15N; 19F); Sonogashira coupling; trifluoromethylpyrazoles